2019
DOI: 10.1177/0020764019850220
|View full text |Cite
|
Sign up to set email alerts
|

Differences in beliefs and attitudes toward Depression and Schizophrenia in Russia and the United States

Abstract: Background: Cross-cultural studies find that culture shapes people’s understanding of mental illnesses, particularly Depression and Schizophrenia. Aims: To compare individuals’ beliefs and attitudes toward Depression and Schizophrenia in Russia and the United States. Method: Participants ( N=607) were presented with vignettes of two diagnostically unlabeled psychiatric case histories and then answered questions regarding mental health literacy (MHL) and attitudes toward the person and the illness. Results: Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 53 publications
7
21
1
Order By: Relevance
“…Our findings of low levels of treatment and diagnosis are consistent with previous studies on attitudes and beliefs about depression where presented with vignettes describing people with symptoms of depression Russian participants compared to participants from Germany [38] and the United States [39] were less likely to attribute depression to biological rather than psycho-social causes [38,39], more likely to indicate depression was related to "weak will" [38,39] and less likely to endorse help seeking for the individual [39], while in a similar comparative study Russian participants were less likely to endorse seeking help from medical sources than British participants and scored lower on a scales indicating tolerance towards descriptions of people with mental health problems [40]. Interventions aimed at improving mental health literacy [41][42][43] and reducing stigma [44,45] both in the general population and among health care professionals could be of benefit in closing the treatment gap.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings of low levels of treatment and diagnosis are consistent with previous studies on attitudes and beliefs about depression where presented with vignettes describing people with symptoms of depression Russian participants compared to participants from Germany [38] and the United States [39] were less likely to attribute depression to biological rather than psycho-social causes [38,39], more likely to indicate depression was related to "weak will" [38,39] and less likely to endorse help seeking for the individual [39], while in a similar comparative study Russian participants were less likely to endorse seeking help from medical sources than British participants and scored lower on a scales indicating tolerance towards descriptions of people with mental health problems [40]. Interventions aimed at improving mental health literacy [41][42][43] and reducing stigma [44,45] both in the general population and among health care professionals could be of benefit in closing the treatment gap.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is concordant with a large sample study conducted with university students in the USA (Eisenberg et al, 2009), as researchers found that personal stigma was higher among more religious students (see also Caplan et al, 2011). Stigma may also be higher in developing or more religious countries; a recent study found that Russian compared to American participants were more likely to view a person depicted in a vignette with depression to be weak-willed and leading an "immoral" lifestyle (Nersessova et al, 2019).…”
Section: Religiosity Stigma and Mhlsupporting
confidence: 81%
“…Diagonally Weighted Least Squares (DWLS) estimator, which is specifically designed for ordinal data, was used. The outliers were winsorized to 3.3 SD from the mean with rank order preserved, a method used in similar research (Nersessova et al, 2019). Correct identification of mental disorders was based on participants' ability to provide the correct diagnosis for either of the two disorders (i.e., major depression for case 1 or a close variation such as depression, and schizophrenia for case 2 or a close variation such as schizophrenic psychosis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations